Voices of first graders: exploratory study on starting school during post-pandemic period - Yuli Kurniawati Sugiyo Pranoto; Diana Diana; Naciye Aksoy; Sugiyo Sugiyo; Aisyah Durrotun Nafisah; Anisa Utamiyanti Tri Rumpoko (Institute of Advanced Engineering and Science, 2024)
The involvement of children’s aspirations is an essential part of educational research that encourages effective learning and well-being among children. Thus, this study aims to promote children’s aspirations of starting schools during the post-pandemic situation. It implemented a face-to-face and online interview involving 63 first graders of primary school level aged seven years, consisting of 24 male and 39 female, by adhering to the prevailing health protocols. The thematic analysis generated two significant findings, including children’s perspectives and their preferences for either face-to-face learning or online learning. With regards to children’s perspectives, this research suggests that children prefer to learn with their teachers and friends at school. Based on the findings, further research is required to explore the responses of children, parents, and teachers to obtain comprehensive data